IoT Based for Monitoring Power Consumption of Electronic Home Appliances - Wulandari, Iswahyuni; Surantha, Nico (International Journal of Artificial Intelligence Research, 2024)
In daily life in various activities, including in households and industry. The Ministry of Energy and Mineral Resources noted that electricity consumption per capita in Indonesia will be 1,173 kWh in 2022. This number has increased by 4.45% from the previous year which was 1,123 kWh. The use of fossil energy sources are increasing as demand increases, making reserves of fossil energy sources increasingly depleted. Nowadays, some measuring tools that sold commercially require wiring process to the MCB, so there is potential danger of electric shock and also the tools can’t store historical data that so the data can’t be analyze. Monitoring electricity usage can help users to alert about household appliances that have been accidentally left on. This is become the research topic by implemented monitoring electrical power consumption in household electronic equipment and storing historical data so users can analyze which electronic equipment with the largest power consumption based on real time and historical data displayed on a Web-based dashboard. Data was taken from testing using the SCT-013 5A 1V Current Transformer Sensor and Arduino Uno R3 microcontroller. Electronic equipment that will be monitored are air conditioner, water heater, washing machine, rice cooker, refrigerator, laptop, dispenser, iron, fan, and lamp. User able to monitor the amount of electrical power consumption used in various electronic equipment and control lamp via Web-based Dashboard.